The energetics of sociality in the molerats (Bathyergidae) - Lovegrove, Barry Gordon (Department of Biological Sciences, 2023)
Primarily, this thesis attempts to resolve the debate concerning the factors selecting for the characteristic physiological traits of subterranean rodents. It also isolates the the probable causes of eusociality within the molerats (Bathyergidae). The bathyergids display the widest range of sociality of all mammals, from strictly solitary genera (Bathyergus, Georychus, Heliophobius), to social and eusocial genera (Cryptomys and Heterocephalus). Sufficient ecological data on key species (e.g., Cryptomys damarensis) were obtained to confirm trends in resource distributions associated with an aridity gradient and increasing sociality. This included data on resource characteristics, seasonal soil and burrow temperature regimes, burrow structures, colony structures, and the activity patterns of C. damarensis. Thermoregulation, including measurements of body temperature (Tb) and resting metabolic rates (RMR), was investigated for Bathyergus, Cryptomys, and Georychus, and compared with data from other workers obtained for Heterocephalus and Heliophobius. The cost of burrowing was measured for C. damarensis and H. glaber